Lung Infection Affects Access to Treatment and Short-Term Outcome in Patients With Severe Alcohol-Related Hepatitis Treated With Corticosteroids. (28th July 2022) - Ntandja Wandji, Line Carolle; Ningarhari, Massih; Lemaître, Elise; Khaldi, Marion; Saffers, Pierre; Lollivier, Julien; Lassailly, Guillaume; Dharancy, Sébastien; Mathurin, Philippe; Louvet, Alexandre
Abstract : INTRODUCTION: Severe alcohol-related hepatitis (AH) is associated with an increased risk of infection, but the impact of pneumonia has not been specifically analyzed in a specific cohort. METHODS: All patients admitted for severe AH between 2002 and 2020 were prospectively included. Systematic screening for infection was performed at admission and renewed in the case of clinical suspicion. RESULTS: We included 614 patients (60.4% men, mean age 49.9 years, median model for end-stage liver disease [MELD] 25.2, bilirubin 18.1 mg/dL), 202 (32.9%) with infections at admission (73 lung infections). Encephalopathy ( P = 0.006), MELD score ( P = 0.0002), and tobacco exposure (past vs never smokers: P = 0.002 or active vs past smokers: P = 0.005) were associated with lung infection at admission on multivariate analysis. Factors independently associated with death before steroid initiation were encephalopathy ( P = 0.003), MELD score ( P = 0.05), and especially lung infection ( P < 0.0001). Thus, patients with a lung infection had a lower probability of receiving steroids than those with other infections and noninfected patients: 54.8 vs 88.4 vs 98.1% ( P < 0.0001). One hundred forty-six of the 558 patients who received corticosteroids developed infection, including 57 (39.04%) pneumonias. The risk of respiratory and nonrespiratory infection was higher in nonresponders to steroids (Lille score ≥0.45) than in responders: 13% vs 7.6%, P = 0.03 and 27.9% vs 10.6%, P < 0.001, respectively. The variables independently associated with 3-month mortality after steroid initiation were lung infection ( P = 0.004), nonresponse to steroids ( P < 0.0001), MELD score ( P = 0.0003), ascites ( P = 0.003), and encephalopathy ( P = 0.018), whereas nonrespiratory infections were not ( P = 0.91). DISCUSSION: Lung infection is frequent during severe AH and influences mortality at admission and after steroid initiation. These results emphasize the need for specific management of lung infection during the course of AH.